A Chlorin e6 derivative-mediated photodynamic therapy versus doxycycline for moderate-to-severe rosacea: A prospective, randomized, controlled study - Yun Wu; Qing Fan; Xiaojing Liu; Yajing Cao; Jin Yang; Yu Yan; Hui Tao; Fuhe Zhang; Linglin Zhang; Peiru Wang; Xiuli Wang (Photodiagnosis and Photodynamic Therapy)
Background: Photodynamic therapy (PDT) is beneficial for managing rosacea, and chlorin e6 derivative-mediated photodynamic therapy (STBF-PDT) has demonstrated efficacy in reducing acne lesions with mild adverse reactions. Objectives: This study aimed to assess the effectiveness and safety of STBF-PDT for the treatment of moderate-to-severe rosacea. Methods: In this prospective, randomised, evaluator-blind controlled study, patients with moderate-to-severe rosacea were assigned to receive up to six STBF-PDT sessions or 100 mg of doxycycline daily for eight weeks, followed by a 24-week follow-up. Results: A total of 76 patients were enrolled (38 assigned to STBF-PDT and 38 to oral doxycycline) with 69 (36 in the STBF-PDT group and 33 in the doxycycline group) completing the study. At the end of treatment, the median reduction in lesion count was 82.3 % in the STBF-PDT group and 81.8 % in the doxycycline group, indicating no significant difference between the groups. The STBF-PDT group exhibited a lower relapse rate and a significantly higher reduction in Demodex mites. Clinician's Erythema Assessment success (CEA), sensations of burning and pruritus, telangiectasia, and Rosacea-related Quality of Life (RosaQoL) scores were comparable between groups. No severe adverse reactions were observed. Conclusions: STBF-PDT is a promising treatment option for mild-to-moderate rosacea with mild adverse reactions.